Mwenda Jean Bosco's comeback (International Library of African Music, 1965)
On the suggestion of Gerhard Kubik, Iwalewa House sent an invitation to the legendary Zairean guitarist Mwenda Jean Bosco (alias Mwenda waBayeke) in May 1982. Bosco, a successful and much admired guitarist and composer in the 1950s and 60s, dropped into virtual oblivion when commercial record companies in Central and East Africa began to publish only electrically amplified bands. It took several years of research (by a few interested people — Gerhard Kubik, Walter Schicho and John Low in particular) even to locate Bosco, who lives alternately in Sakanya, near the Zambian border, and Lubumbashi. Bosco, who writes letters in a flawless, almost ‘ministerial’ style of French, agreed to undertake a European concert tour as a solo guitarist. He came to Europe in May 1982 and had a very successful tour of various cities, Bayreuth, Cologne, Berlin, Graz and Vienna. Observers were surprised that Bosco still plays the old music to perfection, as much as he does the new compositions. His performances were a revelation to many people. Gerhard Kubik who, like David Rycroft and Andrew Tracey, has long admired Bosco’s music writes about his impressions.
Keywords: African Music